Craniofacial anthropometric norms of Malaysian Indians - Ngeow W; Aljunid S (Wolters Kluwer Medknow Publications, 2009)
Objective: This study was done to establish the craniofacial anthropometric norms of the young adult (18- 25 years) Malaysian Indian. Materials and Methods: The study group consisted of convenient samples of 100 healthy volunteers, with equal number of female and male subjects who had no history of mixed racial-parentage. Twenty-two linear measurements were taken twice from 28 landmarks over six craniofacial regions. The methodology and evaluation of indices of the craniofacial region was adapted from Hajnis et al. Results: The minimum measurements are always contributed by the female Indian except for the nose height (n-sn), (left) eye fissure length (ex-en), upper vermillion height (ls-sto), and lower vermillion height (sto-li). There is a gender difference in all the measurements except the (left) eye fissure height (independent t-test; P < 0.05). The Malaysian Indians exhibit some North American White Caucasian (NAWC) features in all regions. The cephalic index indicates a brachycephalic or relatively short wide head with a tendency towards mesocephaly. From the low nasal index, the Malaysian Indian female have a nose that is narrow or leptorrhin similar to the NAWCs. The lower value of the upper lip height to mouth width index in the Indian female indicates a relatively shorter upper lip height compared to the mouth width, also similar to the NAWC. Conclusion: This study establishes the craniofacial anthropometric norms of the Malaysian Indian over 22 parameters. Male in general has a significantly higher measurement than female. The Malaysian Indians do exhibit some NAWC features.